Mobilization and Manipulation of the Cervical Spine in Patients with Cervicogenic Headache: Any Scientific Evidence? - Garcia, Jodan D.; Arnold, Stephen; Tetley, Kylie; Voight, Kiel; Frank, Rachael Anne (Frontiers in Neurology, 2016)
Cervical mobilization and manipulation are frequently used to treat patients diagnosed with cervicogenic headache (CEH), however there is conflicting evidence on the efficacy of these manual therapy techniques. The purpose of this review is to investigate the effects of cervical mobilization and manipulation on pain intensity and headache frequency, compared to traditional physical therapy interventions in patients diagnosed with CEH. A total of 66 relevant studies were originally identified through a review of the literature, and the 25 most suitable articles were fully evaluated via a careful review of the text. Ultimately, ten studies met the inclusion criteria: 1) randomized controlled trial (RCT) or open randomized controlled trial; the study contained at least two separate groups of subjects that were randomly assigned either to a cervical spine mobilization or manipulation or a group that served as a comparison, 2) subjects must have had a diagnosis of CEH; 3) the treatment group received either spinal mobilization or spinal manipulation, while the control group received another physical therapy intervention or placebo control; and 4) the study included headache pain and frequency as outcome measurements. Seven of the ten studies had statistically significant findings that subjects who received mobilization or manipulation interventions experienced improved outcomes or reported fewer symptoms than control subjects. These results suggest that mobilization or manipulation of the cervical spine may be beneficial for individuals who suffer from CEH, although heterogeneity of the studies makes it difficult to generalize the findings.